Astrobioethics: a brief discussion from the epistemological, religious and societal dimension - Chon Torres, Octavio Alfonso (2019)
As astrobiology progresses in its quest to discover life on other planets or to put ourselves in another one, so does its moral problematic. Astrobiology is not only part of natural sciences, but also deals with direct aspects of humanities. For this reason, this paper aims to briefly examine astrobioethics from the epistemological, religious and societal dimension. It also deals with different researches in this regard, in order to better understand the state of the art on this topic and that astrobioethics can help us not only on how we should relate with extraterrestrial lifeforms, but even with terrestrials.